The Role of the Indonesian Government in Implementing REDD (Reducing Emissions from Deforestation and forest Degradation) Program Under Former President Yudhoyono - Johni R.V Korwa (Mandala: Jurnal Ilmu Hubungan Internasional, 2020)
This paper examines the extent to which the Indonesian government has reduced its greenhouse gases emissions coming from deforestation and forest degradation by using REDD program. Such program is highly regarded as a sophisticated instrument to foster collaboration between developing and developed countries in slashing the rate of deforestation. Indonesia itself has enacted the program as a national policy since 2009 under former President Yudhoyono. In this article, the secondary research method is utilized to gather data as well as adopting a qualitative approach to analyse the topic. This paper has found that Indonesia’s policy to curb the emissions from deforestation and forest degradation by conducting REDD program has not yet been successful, because of weaknesses in the implementation. They include the limitation of President’s power in driving policy; the ineffective of information exchange; the inability to do Monitoring, Reporting and Verification (MRV) activities; and contradiction in the decentralization process with regards to REDD implementation. However, some achievements are identified: a slow decline in the rate of deforestation and forest degradation; the continuity partnership between Indonesia and Norway; and the more participation of local stakeholder in supporting REDD program.